The Effect of Diabetic Gymnastics on Reducing Blood Sugar Levels, Stress, and Anxiety in Patients with Type II Diabetes Mellitus - Dewi, Rosliana; Budhiana, Johan; Fatmala, Syiva Dwi; Yulianti, Maria; Arsyi, Dilla Nurul (Universitas Padjadjaran, 2023)
Type II diabetes mellitus (DM) has increased significantly in developing countries, including Indonesia. Type II DM is caused by increasing blood sugar levels. There are various complications both physically and psychologically. Psychological disorders include stress and anxiety. One intervention to reduce blood sugar levels, stress and anxiety is diabetic gymnastics. The purpose of the study was to determine the effect of diabetic gymnastics on reducing blood sugar levels, stress, and anxiety. This type of research uses quasi experiment with pre-test and post-test control group design. The population was type II DM patients with a sample of 36 people divided into control and intervention groups of 18 respondents each using purposive sampling technique. The results of the validity and reliability test of the stress variable referring to the Diabetes Distress Scale-17 were declared valid with r 0.79-0.83 with Cronbach alpha's of 0.921, and the anxiety variable referring to the Depression Anxiety Stress Scales-42 instrument was declared valid with r 0.532 and Cronbach alpha's of 0.943. Data analysis using Paired Sample T-Test and Independent Sample T Test. The results showed that there was an effect of diabetes gymnastics on reducing blood sugar levels, stress and anxiety in the control group (p-value 0.000), (p-value 0.005), (p-value 0.020) and the intervention group (p-value 0.000), (p-value 0.000), (p-value 0.000) and there were differences in the value of reducing blood sugar levels, stress and anxiety in the control and intervention groups (p-value 0.000), (p-value 0.041), (p-value 0.038). Conclusion There is an effect of diabetic gymnastics on reducing blood sugar levels, stress, and anxiety in patients with type II diabetes mellitus. It is expected that diabetes exercises can be used as one of the interventions in dealing with complications of diabetes mellitus. Keywords: Diabetes mellitus, blood sugar level, anxiety, diabetes gymnastics, stress.